A novel approach for content-based mining and indexing using hierarchical ranking - Rupesh, Mishra; Rajesh, Kumar Pathak (I-Manager's Journal on Software Engineering, 2022)
The development of multimedia technologies is becoming more popular; users are not satisfied with traditional information retrieval techniques. People shared ideas and information with others by using methods of communication such as eye contact, movement, interaction through gestures, verbal and written communication. In data recovery, ranking is a key concept. Despite the importance of highlight choosing, calculations for picking ranking models have been thoroughly explored, but this is not the case for highlight choice. Numerous factor-determination methods used in the grouping are directly applicable to ranking. It recovers the natural color, surface, and shape information of images for effective component extraction using edge identification, which is frequently used in signal processing and picture pressure. It has observed the use of information-digging techniques for finding covered-up designs in the enormous dataset and addressing problems in various scientific domains. This paper inputs maximum number of files, and it has voice-based statements or keywords in it. Voice commands convert the voice into text and start searching the text into a file. This will be done by content-based mining, which will be comparable to word-based mining or data mining, using a hierarchy pattern to decide its priority irrespective of its supportive words.